Adoption of conservation agriculturebased technologies in the vertisols in Madhya Pradesh - Sharma, A R; Singh, P K (Indian Farming, 2018)
There is immense scope to promote this technology in the verstiols of central India, for which initiatives must be taken: (i) adopt conservation agriculture-based technologies on-station fully, (ii) large scale demonstrations/on-farm research trials, (iii) trainings and exposure visits to farmers and other stakeholders, (iv) collaboration with multi-stakeholders, (v) subsidy on new farm machinery, (vi) incentives for not burning crop residues, (vi) easy availability of custom hiring services, (vii) good quality and easy availability of herbicides, (viii) policy support, and (ix) skill developments especially in farm machinery.